Dual modification of TiNb2O7 with nitrogen dopants and oxygen vacancies for selective aerobic oxidation of benzylamine to imine under green light. Issue 9 (10th February 2017) - Yu, Zhuobin; Waclawik, Eric R.; Wang, Zhijian; Gu, Xianmo; Yuan, Yong; Zheng, Zhanfeng
Abstract : TiNb2 O7 powder can be modified to an efficient visible light photocatalyst for selective amine oxidation. Abstract : TiNb2 O7 powder was prepared by a simple hydrothermal method and subsequent heat treatment. Vo –N–TiNb2 O7 was generated by NH3 and ethanol dual treatments. The NH3 treatment produced a new N 2p orbital band above the O 2p valence band and oxygen vacancy (Vo ) levels were formed by the ethanol treatment. The photocatalytic performance of modified Vo –N–TiNb2 O7 towards selective aerobic oxidation reactions under green light (475–600 nm, peaked at 525 nm) was measured. It exhibits a high conversion of benzylamine (above 90%) at 80 °C over 24 h with selectivity for N -benzylidenebenzylamine greater than 95% under green light, which is much better than the unmodified and mono-modified TiNb2 O7 . It is suggested that the dual modification alter the electronic band structure of TiNb2 O7 and result in a narrower band gap which should be responsible for the enhanced photocatalytic activity.